Investigation into the surface modification of Ti-6Al-4V to facilitate antimicrobial ionic silver integration for use in implantable orthopaedic devices - Vazirgiantzikis, Iosif (Department of Mechanical Engineering, 2021)
Malignant bone tumours often require a patient to make the choice between limb salvage surgery and complete amputation. The Ti-6Al-4V alloy is the material of choice for implantable orthopaedic devices as it provides a favourable combination of biocompatibility, corrosion resistance and mechanical properties. The only drawback of titanium is that, owing to its bio-inertness, living tissue struggles to attach, creating an opportunity for bacterial adhesion. The “race for the surface” is the term given for the competition between living tissue and bacteria to colonise the implant surface. If bacterial adhesion occurs at a higher rate than tissue adhesion, the chance of infection rises significantly. It has been shown that there is an opportunity to give tissue adhesion the edge by slowing down the initial colonisation of the implant surface by free-swimming bacteria. Silver has a relatively low toxicity level of 28 mg/kg in the body. Current research has focussed mainly on reducing bio-inertness and improving the antimicrobial properties of titanium via the incorporation of silver. In general, the studies conducted on antibacterial surfaces are limited to testing the final sample directly in contact with bacteria, with no attempt to measure silver release rate profiles. The research in this dissertation aimed to investigate methodologies for the incorporation of silver into a modified surface of Ti-6Al-4V in order to facilitate an antimicrobial effect for use in orthopaedic implants. The methodologies investigated were: anodic oxidation of Ti-6Al-4V, followed by silver ion exchange; Ag-doped TiO2 fused to the surface of Ti-6Al-4V via anodic oxidation; and Ag ion implantation into anodically oxidised and polished Ti-6Al-4V. The generated surfaces and sub-surfaces were characterised microstructurally via SEM, FIB, TEM and AFM and chemically by RBS, XRD, AAS and EDS. Ag+ release rate investigations were conducted with the use of ICP-MS. This study was limited to the use of two anodising electrolytes (i.e. 0.5M H2SO4 and 2.1M H3PO4) and altering the AgNO3 concentration (0.05 - 5.0M) and Ag implantation dosage (0.4 - 1.2x1017 ions/cm2 ), where applicable to the method. Results from the Ag ion exchanged samples showed that, microstructurally, the surface produced via anodising in 0.5M H2SO4 and 2.1M H3PO4 were different in terms of pore morphology, Ra, pore homogeneity across the surface and crystal structure. Sub-surface analysis via FIB/TEM found that the ca. 200nm thick TiO2 samples all contained silver nanoparticles (AgNPs). Samples anodised in 0.5M H2SO4 produced an anatase crystal structure, whilst those anodised in 2.1M H3PO4 produced rutile crystal structures. Silver uptake by samples anodised in 0.5M H2SO4 showed decreases in Ag absorption at high (5.0M) AgNO3 ion exchange concentrations, relative to low (0.05M) concentrations. The opposite effect was observed for samples anodised in 2.1M H3PO4. Ag+ release curves corroborated the absorption data by displaying the same trends in terms of Ag+ release post ion exchange. It was concluded that it was a combination of diffusion bottlenecking and higher reactivity of the anatase phase formed during anodising in 0.5M H2SO4 with Ag+ versus the rutile phase that led to these trends. Synthesis of TiO2 powders showed that increasing the AgNO3 concentration (0.05-5M) resulted in AgTiO2 powders with increasing Ag content. Ag-TiO2 powder was successfully fused to the surfaces via anodic oxidation in 0.5M H2SO4 and 2.1M H3PO4 at 100V. Ag-TiO2 powder fused preferentially in areas where downward pressure was present. Microstructurally, the sub-surfaces produced an anodic oxide approximately 200nm thick, to which a significantly thicker, AgNP-containing, TiO2 was attached. XRD data indicated additional Brookite (020) peaks, owing to the presence of the attached Ag-TiO2 powder on the surfaces. Ag-TiO2 powders attached via 0.5M H2SO4 showed a higher overall Ag+ release at all investigated powder concentrations (0.48 - 76.93 wt% Ag) versus those attached via 2.1M H3PO4. This was concluded to be due to the anatase phase produced by 0.5M H2SO4 having greater oxidative power, thus accelerating oxidative dissolution of the AgNPs. RBS data corroborated these trends. Relative to their Ag ion exchange counterparts, the Ag-TiO2 samples had a lower Ag+ release at 0.05M and 0.5M AgNO3 concentrations. However, at 5.0M AgNO3 the Ag-TiO2 samples had a higher Ag+ release. This was the trend irrespective of the anodising electrolyte. Both the anatase and rutile TiO2s showed a reduction in Ra post Ag ion implantation and the polished Ti6Al4V samples showed an increase in Ra. This was due to preferential erosion of areas with high free surface energy. In the case of both TiO2s these were “high points” in the oxide and for polished Ti6Al4V these were the grain boundaries. Both TiO2s were amorphised during ion implantation. All ion implanted TiO2 showed the presence of AgNPs within the first 50nm of the surface. These AgNPs increased in size as the implantation dosage was increased. Polished Ti6Al4V showed no AgNP formation but EDS mapping confirmed that the silver was also located 50nm within the surface. TiO2 Ag+ release was similar for both implantation dosages because the surfaces had been supersaturated at the low dose, thus an increase in implantation dose had no significant effect on further silver uptake. The release rates were also similar between the oxides because of amorphisation. Polished Ti6Al4V showed an increase in Ag uptake and Ag+ release when the implantation dose was increased. RBS results corroborated the observed Ag+ release results. In comparison, both the ion exchanged samples and the Ag-TiO2 fused samples showed performances in similar ranges of Ag+ release. The Ag-TiO2 samples showed a greater degree of tailorability of the Ag+ release, whereas the ion exchanged samples showed a lesser sensitivity to an increase in AgNO3 concentration. Ag ion implanted samples showed an order of magnitude lower Ag+ release relative to the other studied methods. In comparison to literature, all ion exchanged and Ag-TiO2 samples had the potential to have a 100% antimicrobial effect (AE). Ion implanted oxides had a 55-100% potential, while the polished Ti6Al4V had a 55% AE at low dose and a 100% AE at high dose. In order to achieve maximum silver ion release and the associated antimicrobial effect, the technique of Ag-TiO2 fused to the surface using the 2.1M H3PO4 and 0.5M H2SO4 electrolytes yielded the best results, with a silver ion release of 550 and 600 ppb respectively over two weeks. This technique also satisfied the research aim, in that the methodology offered a combination of tailorability of silver release and commercial scalability.